1999
DOI: 10.1111/1467-8721.00033
|View full text |Cite
|
Sign up to set email alerts
|

Happy as an Extraverted Clam?

Abstract: Personality characteristics, especially the traits of extraversion and neuroticism, have been proposed as the primary determinant of subjective wellbeing (SWB). Meta-analytic evidence presented here suggests that personality is indeed strongly related with SWB, and that only health is more strongly correlated with SWB. In a study of 137 personality traits that have been correlated with SWB, neuroticism was one of the strongest negative correlates of SWB. However, extraversion was not the primary factor associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(10 citation statements)
references
References 11 publications
2
7
1
Order By: Relevance
“…This is in line with previous studies showing that self-esteem is correlated with subjective well-being (Ayyash & Alamuddin 2007;Benet-Martínez & Karakitapoğlu-Aygun, 2003;DeNeve, 1999;Lucas, 2008;Raboteg-Šarić et al, 2008;Schimmack & Diener, 2003;Purnama, 2006). People with high level of self-esteem will have high level of subjective well-being as well.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with previous studies showing that self-esteem is correlated with subjective well-being (Ayyash & Alamuddin 2007;Benet-Martínez & Karakitapoğlu-Aygun, 2003;DeNeve, 1999;Lucas, 2008;Raboteg-Šarić et al, 2008;Schimmack & Diener, 2003;Purnama, 2006). People with high level of self-esteem will have high level of subjective well-being as well.…”
Section: Discussionsupporting
confidence: 92%
“…This in turn could promote their integration into the life story. Extraversion did not predict growth in any of our models, but it is also usually associated with low neuroticism and higher subjective well-being (DeNeve, 1999). This could suggest that high extraversion actually is a predictor of resilience, and a recent study has shown that resilience has an inverse relationship with posttraumatic growth (Levine et al, 2009).…”
Section: Discussioncontrasting
confidence: 58%
“…This confirms the results of (Harris, English, Harms, Gross, & Jackson, 2017;Hoorn, 2007;Veenhoven, 2006) which revealed that extraverts report feeling happy and satisfied with life when compared to other categories of personality traits, specifically neuroticism. This has been emphasized by (Deneve, 1999;Diener et al, 1999;Veenhoven, 2016)'s studies which revealed that extraverted people are less depressed, and they express more their thankfulness than neurotic people. Finally, the findings of the current research replicate the one carried out by Sujarwoto et al (2017), which have shown that extraversion personality trait is significantly connected to life satisfaction and happiness.…”
Section: Discussionmentioning
confidence: 99%